The Potential of Asynchronous Podcasting in Developing EFL Learners’ Communicative Competence - Dziura, Anna (Uniwersytet Rzeszowski, 2023)
Nauka mówienia w ogóle, a szczególnie nauczanie mówienia w języku obcym to proces, który ma kluczowe znaczenie nie tylko jako wykształcenie umiejętności mówienia, ale jako proces, który ma na celu zaistnienie zjawiska komunikacji. Dlatego ucząc się języka, istotną kwestię stanowi kompetencja komunikacyjna, której rozwój i doskonalenie to cel nauczania i uczenia się. Ucząc się języka, można z łatwością korzystać z różnych narzędzi i zasobów cyfrowych. Niniejsza rozprawa jest próbą zbadania zależności pomiędzy rozwijaniem ustnej kompetencji komunikacyjnej, a wykorzystaniem asynchronicznych narzędzi do nagrywania głosu w celu tworzenia własnych podcastów przez uczących się języka angielskiego jako obcego. Opierając się na wynikach badań przeprowadzonych w ramach niniejszej rozprawy, odnosząc się do ustnej kompetencji komunikacyjnej uczniów, należy stwierdzić, iż umiejętne włączenie podcastów w proces nauczania mówienia przyczynia się do rozwijania kompetencji komunikacyjnej uczniów, znacząco rozwijając ich sprawność komunikacyjną, poprawność językową, wymowę, jak i zakres stosowanych środków językowych, jednocześnie budując przyjazne środowisko nauczania i uczenia się, promuje ich autonomię. Ponadto, pozytywnie wpływa na przygotowywanie się uczniów do egzaminu zewnętrznego.

Learning to speak in general, and teaching to speak a foreign language in particular, is a process that is crucial not only as a development of speaking skills, but as a process to make the phenomenon of communication occur. Therefore, when learning a language, an important issue is communicative competence, whose development and improvement is the goal of teaching and learning. When learning a language, you can easily use a variety of tools and digital resources, including pre-made, random, or specially prepared for educational purposes podcasts. The main purpose of this dissertation is to test the appropriateness of the assumption that the creation of their own podcasts by learners of English as a foreign language affects the development of oral communicative competence in the language. On the basis of the research results, referring to the oral communicative competence of students, it should be said that the skilful integration of podcasts into the process of teaching speaking contributes to the development of students' communicative competence. It also significantly develops their communicative proficiency, linguistic correctness, pronunciation, and the range of linguistic means used, while building a friendly teaching and learning environment, promotes their autonomy. In addition, creating their own podcasts helps students prepare for the oral English final exam and has an impact on students' performance on the exam.
Wykorzystanie asynchronicznych narzędzi do nagrywania głosu i ich wpływ na rozwijanie kompetencji komunikacyjnej uczących się języka angielskiego jako obcego
Promotor: dr hab. Anna Turula, prof. UP - 215 s.
Keywords: podcast; narzędzia asynchroniczne; kompetencja komunikacyjna; asynchronous tools; communicative competence